SILICA-RICH WASTE TO SUSTAINABLE NANOFIBERS VIA ELECTROSPINNING: A SYSTEMATIC REVIEW - Lumbanraja, Louis; Syafriadi, Syafriadi (International Journal of Multidisciplinary Research and Literature, 2025)
Often overlooked in conventional waste management systems, silica-rich waste holds untapped potential as a sustainable precursor for advanced nanomaterials. This systematic review critically examines how diverse industrial and agricultural silica-rich residues such as rice husk ash, glass waste, and geothermal sludge can be valorized into functional nanofibers via electrospinning. Applying the PRISMA framework, 150 peer-reviewed studies (2014–2024) were synthesized to map current research on waste selection, silica extraction methods, electrospinning parameters, and end-use performance. The review highlights that tailored purification routes can yield high-purity silica suitable for stable, defect-free nanofibers. Electrospinning success hinges on a fine-tuned interplay of solution properties, operational settings, and ambient conditions. Resulting nanofibers demonstrate outstanding performance in air/water filtration, biomedical scaffolding, and energy storage systems. However, raw material variability, process reproducibility, and scale-up potential persist. By integrating material science with circular economy principles, this work positions waste-derived nanofibers as a strategic pathway toward greener, high-value applications in resource-constrained settings.